Swedish private-sector employees’ experiences of promoting and hindering factors for working while having mental health problems: A qualitative study - Anna Frantz; Iben Axén; Gunnar Bergström; Anna Finnes; Elisabeth Björk Brämberg (PLoS ONE, 2026)
Objectives The workplace is an important arena for identifying and managing early symptoms of mental health problems. This study aimed to explore how private sector employees at risk of sickness absence due to mental health problems experienced promoting and hindering factors for working. Methods Semi-structured interviews were conducted with 18 employees with mental health problems (≥3 on the General Health Questionnaire or who answered yes to a question on self-predicted sickness absence in the coming year due to common mental disorders). Reflexive thematic analysis was used to analyze the data. Results The analysis resulted in three themes: influence of life stage on working while having mental health problems; managing mental health problems in the social and organizational context; and preserving one’s identity and agency when working while having mental health problems. Promoting and hindering factors occurred at the individual, group, leader and organizational levels. Promoting factors included social support from colleagues, a trusting relationship with the first-line manager, and engaging in leisure-time physical activity. Hindering factors included perceiving the cause of symptoms to be primarily outside work leading to delayed access to help, a cold or noisy work environment, and schedule mismatch. Conclusion Promoting and hindering factors occurred at multiple levels. Fostering a supportive and inclusive work environment where there is space for enjoyment can help employees manage mental health problems at work. Other promoting factors include having an active and present manager, reasonable production goals, and leisure-time physical activity. Employees who perceive the cause of their symptoms to be related to their private life tend not to seek help from the workplace, despite the impact on their work. This should be considered in the development of future interventions. Our study supports a life-course perspective on the understanding of how employees experience promoting and hindering factors for working while having mental health problems.